Three Cases of Exclusively Extragenital Canine Transmissible Venereal Tumor (cTVT) - Veloso, Jéssica Fontes; Oliveira, Thais Nascimento de Andrade; Andrade, Lorena Priscila; Silva, Fabiana Lessa; Sampaio, Katia Moema Oliveira Rosa; Michel, Ana Flávia Ribeiro Machado; de Lavor, Mário Sergio Lima; Carlos, Renata Santiago Alberto (Acta Scientiae Veterinariae, 2018)
Background: Canine Transmissible Venereal Tumor (cTVT) is a neoplasia that affects mainly the genital organs of dogs, but can rich extragenital sites as well. It´s a tumor characterized microscopically by the presence of vacuolized round cells. Transmission occurs by implantation of these cells in non-affected tissues and the treatment is based on vincristine chemotherapy. Cases: Case 1. A 5-year-old intact male Poodle, presenting an increase volume of nasal plane came for veterinary care at a private veterinary clinic. The animal had bilateral bloody nasal secretion and dyspnea. The external genitalia had no alterations. The cytological evaluation confirmed cTVT. Treatment with vincristine sulfate weekly showed a rapid response with improvement of the respiratory condition, total remission of the mass and absence of neoplastic cells in cytology. Case 2. A 5-year-old mixed-breed canine bitch, weighing 6.7 kg, was brought to the State University of Santa Cruz Veterinary Hospital (UESC-VH), showing an increase volume in the nasal plan region, with complaints about sneezing, nasal bleeding, respiratory distress with approximately 4 months of evolution. The owner informed that the mother of these female dog, that lived in the same environment, died a month before the beginning of clinical signs of the bitch of this case, and showed a reddish vaginal mass with intense bleeding. Intranasal exfoliative cytology showed moderately cellular sample compatible with cTVT. The treatment with vincristine sulphate for 6 weeks, showed completely remission of all clinical signs. Case 3. A 3-year-old mixed-breed male dog was brought to the UESC-VH with a reddish, friable mass located in the left eye. The citology confirmed the clinical suspicion of cTVT. After six weekly sessions of chemotherapy with vincristine sulfate, the tumor regressed and a new cytological evaluation was performed, without visible of tumor cells. By the end of the treatment, the dog was diagnosed with phitisis bulbi, and one year later, due to recurrent ulcerative keratitis, the enucleation was performed and the histopathological examination of the eye did not identify the presence of tumor cells. Discussion: Two of the dogs cited in this report had freely streets access, without supervision of the owners, and they are likely to have contracted cTVT on one of those occasions. The animal’s care style acts as a risk factor for the development of neoplasia. Regarding the third animal, the close contact with another female dog, who had compatible vaginal cTVT clinical signs was probably the factor that determined the transmission. None of the animals cited in this report had lesions on their external genitalia. The extragenital presentation may be attributed to the social behavior of licking and sniffing the genitalia of carrier animals, which may lead to the natural implantation of the viable cells of the cTVT into the ocular and nasal mucosa. About the clinical signs manifested, in the cases of involvement of the nasal structures, the main signs described in literature are bloody nasal secretion, sneezing, dyspnea and increased nasal plane volume, and are similar to those observed in the animals cited in this report. In the case of ocular cTVT, the increase volume with impairment and deformity of all ocular structures, as well as pain and pruritus corroborate with the clinical findings observed in the literature. The cytopathological test was the diagnostic tool used in all cases cited in this report and the cytopathological findings corroborates with those described in the literature. Vincristine sulfate is the drug of choice for the treatment of cTVT cases, and in the dogs of this report, this drug was successfully used leading to complete remission of lesions and clinical signs, as observed in other studies. Keywords: nasal mucosa, ocular mucosa, venereal disease, round cells.